Patents and the Technological Performance of District Firms Evidence for the Emilia-Romagna Region of Italy - Enrico Santarelli (Max Planck Institute for Research into Economic Systems, 2004)
This paper investigates some crucial aspects of the recent development of industrial districts in the Emilia-Romagna region of Italy, where this type of spatial agglomeration of industrial firms has flourished since the period immediately after the Second World War. In particular, it is aimed at comparing the technological strength (in terms of patents registered with the European Patent Office) of innovative firms located within and outside industrial districts, in order to determine whether the prediction that innovative activity favors those firms or industries with direct access to knowledge producing inputs applies also to the case of industrial districts in the Emilia-Romagna region. The analysis deals with the population of firms with their headquarters in the region which registered at least one patent with the European Patent Office during the 1986-1995 period. Results from panel model estimates show that being located within an industrial district resulted in a technological advantage during the overall 1986-1995 period. However, on breaking down this period into two sub-periods (1986-1990 and 1991-1995) it is found that such advantage was strong in the first one, whereas it was lost in the first half of the 1990s.
Keywords: R12; R15; R11; 330; Innovation; Patent; Unternehmensentwicklung; Industriegebiet; Regionale Konzentration; Schätzung; Emilia-Romagna; Italien